A computer-aided educational tool for induction motors - Gencer, Cetin; Gedikpinar, Mehmet (Wiley, 2012)
The computer-aided educational tools have gained popularity in the last years with successful implementation in many areas, including in engineering education. These tools are aimed to help the students for visualization of the concepts and to provide the graphical feedback during the learning process. This paper presents a computer-aided educational tool for induction motors, which is a part of laboratories in the electrical machinery courses. This tool helps to students and educators in subject to teaching/of the equivalent circuit, and the vector/phasor diagrams in induction motors. The tool software was prepared in DELPHI environment. It has flexible structure which is enable to users to change motor label values, and to solve equivalent circuit parameters and winding account. The proposed educational tool was utilized in laboratories of electric machinery courses and well received by students. (c) 2010 Wiley Periodicals, Inc. Comput Appl Eng Educ 20: 503509, 2012
Keywords: computer-aided educational tool; induction motor; equivalent circuit; DELPHI